VD_FINDINFO HC / 2013 / 286 vom 25. April 2013 - VD Tribunal cantonal (2013)
BAIL À LOYER, RESTITUTIONEN GÉNÉRAL, INDEMNITÉEN GÉNÉRAL, AVIS DES DÉFAUTS | 267 al. 1 CO, 267a al. 1 CO, 319 let. a CPC (CH), 58 al. 1 CPC (CH)